Estudo numérico do escoamento bifásico líquido sedimento empregando o método Smoothed Particle Hydrodynamics (SPH) - NASCIMENTO, Erick Oliveira do (Instituto de Engenharia e Geociências, 2024)
The present work clari es the lagrangian numerical metho d Smo othed Particles Hydro dynamics (SPH) that do e sn' t have meshes i n it's discretiza ti on and in the last decades has attracted the attention. When compared to other conventional metho ds in the eld of computational uid dynamics (CFD), the SPH approach demonstrates advantages in multiphase problems and matter transp ort due to it's ease in de aling with complex b oundaries and their relatively simple physical mo deli ng . The multi-phase and two-dimensional numerical co de of DualSPHysics was tested and compared with the exp erimental mo del of a canal in which the sliding of glass spheres o ccurs on a wate r slide, in order to replicate in a simpli sti c way the phenomenon of uvial erosion that o ccurs recurrently in the Amazon region that end up generating havo c for the riverside due to the large amount of energy that the generated waves have due to the impact of the sediment with the river b ed and the lack of contai nment plans and decision making. I t was p ossible to observe that through the use of a Graphic al Pro ce ssing Unit (GPU) it is p ossible to simulate num erically the wave generated by the c ollision of the exp erimental m o del.